المقاصد الحاجية وأثرها في التقعيد الأصولي والفقهي - الجموعي, هاني (Universty of Eloued جامعة الشهيد حمه لخضر, 2021)
الملخص: هذه الدراسة بعنوان: "المقاصد الحاجية وأثرها في التقعيد الأصولي والفقهي"، كان إشكالها الرئيس الذي تسعى للإجابة عنه هو: ما حقيقة المقاصد الحاجية؟ وما هي القواعد الأصولية والقواعد والضوابط الفقهية التي بُنيت في تقعيدها على اعتبار المقاصد الحاجية؟ أجابت الدراسة عن ذلك من خلال ثلاثة فصول، خُصِّص الفصل الأول لبيان حقيقة المقاصد الحاجية وما يرتبط بها، ولمعنى التقعيد الأصولي والفقهي وما يتصل بكلٍّ منهما، وجُعِل الفصل الثاني لأثر المقاصد الحاجية في التقعيد الأصولي، والفصل الثالث لأثر المقاصد الحاجية في التقعيد الفقهي. وتوصّلت الدراسة لجملة من النتائج لعل من أهمها أنّ المقاصد الحاجية قد أثّرت في تقعيد طائفة من القواعد الأصولية والقواعد والضوابط الفقهية، وأنّ الأصوليين والفقهاء لم يُغفلوا النظر في مراعاة المقصد الحاجي -الذي يدور معناه حول جانبِ التيسير ورفعِ الحرج، وتمسّ الحاجة إليه في عبادات الناس ومعاملاتهم- حين صياغتهم للقواعد الأصولية والفقهية، وقد جاء تقعيدهم في الغالب معبِّرا تصريحا لا تلميحا على هذا النظر المصلحي الحاجي. كما أوصت الدراسة بتتبع القواعد الأصولية أو القواعد والضوابط الفقهية التي بُنيت في تقعيدها على المقاصد الحاجية في مصنفات بعض العلماء واستخراجها ودراستها في رسائل أكاديمية، وتوسيع البحوث المتعلقة بنظرية الحاجة على غرار البحوث المتعلقة بنظرية الضرورة. Résumé : انجلزية The study is entitled: "The whole need objectives and their effect on the fundamentalist and jurisprudential setting". The problematic seeks to answer this questions: What is the reality of the whole need objectives? What are the fundamentalist rules, jurisprudential rules and its regulations which based in their setting on the consideration of the whole need objectives? The study responded to this through three chapters, The first one is devoted to clarifying the meaning of the whole need objectives, and the meaning of fundamental and jurisprudential setting and everything related to them.the second chapter is about the effect of the whole need objectives on the fundamental setting, while the therd one talk about the effect of it in the jurisprudence setting The study reached a set of results, the most important ones are that the whole need objectives influenced the fundamentalist rules and the jurisprudential regulations and that the scholars and the diligents did not neglect to concederate the whole need objectives -which concerned by the facilitation and raising the embarrassment, and the need for it in the people's worship and their dealings- in the fundamental and jurisprudential setting,their setting came mostly to express directly the needy and the adventageous consideration.the study recommended to follow the fundamental rules or jurisprudential regulations based in their setting on the whole need objectives in the works of some scholars and extracting, studying them in academic theses, and to expand the research related to the needs theory, such as the researchs about the nessessity theory .
أطروحة دكتوراه تخصص الفقه و أصوله في العلوم الإسلامية
Keywords: المقاصد، الحاجية، التقعيد، الأصولي، الفقهي; objectives fundamentalist , setting, Jurisprudential